Outcome of Femoral Neck Fracture in Elderly Patient Treated by Austien Moore Prosthesis in Ahwaz Imam khomeyni and Razi Hospital Since 2006-2010 - Nasser Sarrafan; Seyed Abdolhossein Mehdi Nasab; Mohsen Gholami (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: Femoral neck fracture (FNF) is one of the most common fractures in elderly patients. There are a variety of treatment for this fracture the aim of this study was to evaluate the Results of FNF with Austin moore prosthesis.Subjects and Methods: This Retrospective - prospective study was performed from 2005 to 2010 and 126 patients (73 femel,53 male) with a mean age of 78 years range (44-100y)were operated in two hospitals (Emamkhomeini andRazi).A.M prosthesis was used in all patients and the mean follow-up-time was 4 years (1-6y)Results: The mortality rate during the first 1-2 years was 27.7%(35 patiants) Forty five patients (35/7%) had hip pain , and .13 patients(10/3%) sustained infection. Periprostetic fracture were occurred in 2 (1/5%) Cases of dislocation and lossening in 4(3/17%) patients.Conclusion: Treatment of femoral neck fracture in elderly patients was associated with a considerable rate of complications and mortality. Chronic pain was the most common complication.Moore prosthesis is a cheap device, and in spite of its complications, it is still used Despite of its complication’ it still use for elderly patients with femoral neck fractures who have a minimum daily activity.